The Effect of Ashitaba (Angelica keiskei (Miq.) Koidz.)) Sap on the Total Cholesterol Levels of Cisplatin-Induced Wistar Rats - Wahyuni, Ika; Aulifa, Diah L.; Rosdianto, Aziiz M.; Levita, Jutti (Universitas Padjadjaran, Indonesia, 2023)
Cisplatin is a platinum-based anticancer drug that, in long-term use, causes nephrotoxicity due to oxidative stress and increases total cholesterol and triglycerides in animal models. Angelica keiskei (Miq.) Koidz., (A. keiskei) or Japanese celery ashitaba, has been reported for its antioxidant and nephroprotective activity. This study aims to determine the activity of A. keiskei sap on total cholesterol levels of cisplatin-induced Wistar rats. The sap of A. keiskeiwas freeze-dried until a yield of 3.62% w/v was obtained. The fat content in A. keiskei sap powder was obtained at 7.36%. A total of 60 g of A. keiskei sap powder was macerated with 96% ethanol solvent (1:10) for 5 x 24 h until the ethanol extract of A. keiskei sap (ASEE) of 82.08% w/w was obtained. The pharmacology activity was conducted on male Wistar rats, which were divided into 5 groups, namely normal (treated with CMC Na 0.3%), negative (nephrotoxicity induced with cisplatin 5 mg/kg BW), positive (nephrotoxicity induced with cisplatin 5 mg/kg BW and treated with quercetin 20 mg/kg BW), and two test groups which were nephrotoxicity induced with cisplatin 5 mg/kg body weight and treated with ASEE 1000 mg/kg BW, and ASEE 1500 mg/ kg BW. It was found that neither dose of ASEE altered the total cholesterol levels in cisplatin-induced male Wistar rats and could maintain the cholesterol levels in the normal range.